Theoretical and methodological aspects of the study of monuments of the Botai culture (1980-2014) (Journal of history, 2022)
More than 40 years of scientific research on the sites of the Botai archaeological culture have created a huge theoretical material based on the findings of the North Kazakhstan (SKAE), Kokshetau (KAE) and Botai International Archaeological Expeditions (BMAE). The first years of archaeological research at the Botai monument gave a huge number of scientific hypotheses and conclusions, which were confirmed at a later time using modern scientific research methods. In 1980, the number of housing depressions and traces of structures was 80 marks, by 2020, using modern technologies and the method of geomagnetic survey, the number of depressions was 150. In the modern archaeological science of Kazakhstan and the world, certain aspects of the achievements of the ancient bearers of the Botai archaeological culture are questioned. The scientific fact that the Botai population was the first to domesticate the wild steppe horse is called into question. That the fact of the first domestication of a horse in world civilization occurred on the territory of the Southern Urals. This statement is also supported by a part of Kazakhstani archaeologists. At the present stage, archaeologists are faced with the task of structuring scientific results in the reports of the SCAE, KAE, BMAE, determining the exact sites of archaeological excavations at the Botai site by years, and comparative analysis of archaeological material. Key words: archeology, history, Botai, Northern Kazakhstan.